Measuring the innovation performance of Malaysian automotive industry - Nurul Fadly Habidin,; Suzaituladwini Hashim,; Zuraidah Zainol,; Wan Salmuni Wan Mustaffa,; Yong, Sharon Yee Ong; Norlaile Salleh Hudin, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
Innovation is an important element in the manufacturing industry as it assists the organization to become more competitive in the market. To obtain some insight into the innovation performance of Malaysian automotive industry, this study examined three innovation performance measures of environmental innovation, employee innovation, and technology innovation. As many as 400 questionnaires were distributed to top management in the Malaysian automotive industry and a total of 229 completed questionnaires was obtained representing a response rate of 57.25%. The results of the factor analysis verified and validated all three innovation performance measures.